Quasistatic Cyclic Tests and Finite Element Analysis of Low-Aspect Ratio Double Steel Concrete Composite Walls - Kaize Ma; Yudong Ma; Boquan Liu (Advances in Civil Engineering)
An innovative double steel concrete (DSC) composite wall was developed to enhance constructability and lateral load resistance of buildings. Three low-aspect ratio DSC composite walls were constructed and tested to study the shear behavior. Under different testing parameters, the failure modes, hysteresis behavior, lateral load resisting capacity, deformation, and energy dissipation of the composite walls were observed. The results showed that all specimens failed in shear behavior with steel plate buckling and concrete compressive crushing. The pinching behavior was obvious for hysteresis loops of composite walls. Moreover, the lateral load resisting capacity and deformation were significantly affected with axial compression ratio and steel ratio. Beyond that, the ductility coefficients of specimens reached 3.30. The finite element (FE) method was performed to analyze the failure process of the specimens with cyclic analysis. The concrete damage plastic model (CPDM) was selected to simulate the damage progress of concrete. Validation of the FE models against the experimental results showed good agreement.